Investigation of the Opinions of Experts and Managers in the Regional Water Organization and the Water and Wastewater Company of East Azerbaijan regarding the impact of the Coronavirus on Water Resources and Facilities - Mohammad Mosaferi; Reza Yegani; Neda Gilani*; Abolfazl Majnooni-Heris; Ahmad fakherifard; Nasimolzahra Toghyanian; Hossein Samadi Vakil; Rana Naderi; Sara Nikmaram; Ali Jalilizadeh; Fereydoon Armanfar (Mazandaran University of Medical Sciences, 2023)
Introduction and purpose: Water is a key element in hygiene during the COVID-19 pandemic. The present s tudy aimed to survey the opinions regarding the possible impact of Coronavirus on water and wastewater sources and facilities. Methods: The experts and managers of the Regional Water Organization and the Water and Wastewater Company were surveyed using a checklist  (ranking-descriptive) in the present cross-sectional descriptive s tudy. One-sample and two-sample chi-square tests and non-parametric Mann-Whitney test were used for s tatis tical analysis. Results: In total, 70.9% of participants believed that the outbreak of COVID-19 affected the water resources and facilities in terms of consumption and supply while increasing the consumption (93.2%) and creating a significant challenge in supply (83%) had des tructive effects on other uses, especially agriculture (22.7%). Also, 92.3% believed that managing urban water consumption during the Corona outbreak and modifying the consumption pattern is necessary. The need for more preparation (79.6%), funding (86.8%), and training (96.8%) was recommended. Regular monitoring of water was emphasized by 70.9% of the participants. It is noteworthy that only 50.4% of the respondents believed that the treatment done on the water in the water treatment plants can control the coronavirus. Conclusion: The performance of managers and experts regarding water sources and facilities is a function of their beliefs regarding the impact of the COVID-19 outbreak. About 50% of the participants failed to believe in the effectiveness of the exis ting water treatment in deactivating the coronavirus. Also, specialized training is recommended to increase knowledge.